2019
DOI: 10.1007/s00213-019-05230-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of microbiota and inflammation in self-judgement and empathy: implications for understanding the brain-gut-microbiome axis in depression

Abstract: Rationale The gut-brain axis includes bidirectional communication between intestinal microbiota and the central nervous system. Bifidobacterium and Lactobacillus spp. have been implicated in psychological health, such as depression, through various pathways (e.g. inflammation). Research needs a better understanding of direct and indirect effects through examination of psychological factors that make people susceptible to, or offer protection ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 52 publications
0
45
0
3
Order By: Relevance
“…Microbiota would impact behavior via bottomup pathways, positioning it as a factor to consider in studies attempting the understanding of well-being (O'mahony et al, 2009;Dinan and Cryan, 2012;Dinan et al, 2013). Moreover, increasing evidence has posited microbiota as relevant in the context of autism (Mulle et al, 2013;Sgritta et al, 2019), schizophrenia (Severance et al, 2016), multiple sclerosis (Jangi et al, 2016), bipolar disorder (Evans et al, 2017), irritable bowel disease (Jeffery et al, 2012;Kennedy et al, 2014), obesity (Gomes et al, 2018), neurodegenerative disorders (Boehme et al, 2019), and depression (Naseribafrouei et al, 2014;Jiang et al, 2015;Aizawa et al, 2016;Kelly et al, 2016;Heym et al, 2019). The mechanisms through which microbiota exert its effects over behavior include neural pathways via the vagus nerve, regulation of the stress response, production of short chain fatty acids after fiber fermentation, amino acids metabolism and control of immune function, among others (Cryan and Dinan, 2012;.…”
Section: Gut Microbiota Influence Behaviormentioning
confidence: 99%
“…Microbiota would impact behavior via bottomup pathways, positioning it as a factor to consider in studies attempting the understanding of well-being (O'mahony et al, 2009;Dinan and Cryan, 2012;Dinan et al, 2013). Moreover, increasing evidence has posited microbiota as relevant in the context of autism (Mulle et al, 2013;Sgritta et al, 2019), schizophrenia (Severance et al, 2016), multiple sclerosis (Jangi et al, 2016), bipolar disorder (Evans et al, 2017), irritable bowel disease (Jeffery et al, 2012;Kennedy et al, 2014), obesity (Gomes et al, 2018), neurodegenerative disorders (Boehme et al, 2019), and depression (Naseribafrouei et al, 2014;Jiang et al, 2015;Aizawa et al, 2016;Kelly et al, 2016;Heym et al, 2019). The mechanisms through which microbiota exert its effects over behavior include neural pathways via the vagus nerve, regulation of the stress response, production of short chain fatty acids after fiber fermentation, amino acids metabolism and control of immune function, among others (Cryan and Dinan, 2012;.…”
Section: Gut Microbiota Influence Behaviormentioning
confidence: 99%
“…With one microbial cell to match each human cell, and impressive numbers of functional microbial genes (quite capable of influencing disease risk as well as vitality [68]), humans are indeed multi-species entities [69,70]. Consider the implications of just a single non-pathogenic microbial strain influencing brain activity during social stress [71] or findings that suggest that our microbial partners could be putting their "weight" on the scale of human cognitive empathy [72] and personality [73]. Moreover, these observations open a door to narrative around very personal biological consequences of large-scale biodiversity loss [63].…”
Section: Extinction Of Biological Experiencementioning
confidence: 99%
“…In addition, it was shown that WD-fed mice had intestinal dysbiosis, which was accompanied by inflammatory signaling in the brain, microglial activation, and reduced neuroplasticity [83]. Therefore, dysbiosis of gut microbiota may increase the cytokines production and neuroinflammation, affecting mood, or it could induce psychiatric disorders such as depression and anxiety as was described in animal models [56] as well as in comparative studies performed in humans [5,84]. Moreover, in maternal immune activation (MIA) mouse model, intestinal dysbiosis induced both higher production of both 4-ethylphenylsulfate (4EPS) and indolepyruvate, leading to autism spectrum disorder (ASD).…”
Section: Dysbiosis and Its Effect On The Neuroplasticity And Behaviormentioning
confidence: 99%